Detailed assessment of benefits and risks of retrievable inferior vena cava filters on patients with complicated injuries: the da Vinci multicentre randomised controlled trial study protocol. Issue 7 (12th July 2017) - Ho, Kwok M; Rao, Sudhakar; Honeybul, Stephen; Zellweger, Rene; Wibrow, Bradley; Lipman, Jeffrey; Holley, Anthony; Kop, Alan; Geelhoed, Elizabeth; Corcoran, Tomas
Abstract : Introduction: Retrievable inferior vena cava (IVC) filters have been increasingly used in patients with major trauma who have contraindications to anticoagulant prophylaxis as a primary prophylactic measure against venous thromboembolism (VTE). The benefits, risks and cost-effectiveness of such strategy are uncertain. Methods and analysis: Patients with major trauma, defined by an estimated Injury Severity Score >15, who have contraindications to anticoagulant VTE prophylaxis within 72 hours of hospitalisation to the study centre will be eligible for this randomised multicentre controlled trial. After obtaining consent from patients, or the persons responsible for the patients, study patients are randomly allocated to either control or IVC filter, within 72 hours of trauma admission, in a 1:1 ratio by permuted blocks stratified by study centre. The primary outcomes are (1) the composite endpoint of (A) pulmonary embolism (PE) as demonstrated by CT pulmonary angiography, high probability ventilation/perfusion scan, transoesophageal echocardiography (by showing clots within pulmonary arterial trunk), pulmonary angiography or postmortem examination during the same hospitalisation or 90-day after trauma whichever is earlier and (B) hospital mortality; and (2) the total cost of treatment including the costs of an IVC filter, total number of CT and ultrasound scans required, length of intensive care unit and hospital stay, procedures and drugs required to treat PE or complications related to the IVC filters. The study started in June 2015 and the final enrolment target is 240 patients. No interim analysis is planned; incidence of fatal PE is used as safety stopping rule for the trial. Ethics and dissemination: Ethics approval was obtained in all four participating centres in Australia. Results of the main trial and each of the secondary endpoints will be submitted for publication in a peer-reviewed journal. Trial registration number: ACTRN12614000963628; Pre-results.